The Quality of Communication in the Context of Regional Development - Lenka Ližbetinová (DETUROPE)
Public administration of the Czech Republic is currently in the process of improving services by introducing systems and principles of quality management. This process is also supported by the New Strategic Framework for the Development of Public Administration of the Czech Republic for the period 2014 -2020th and the National Strategy for Quality Policy in the Czech Republic for the period 2011 to 2015th. The issue of regional development depends on functional and effective cooperation between public authorities, business portfolio and the public. Implementation of individual projects aimed at regional development cannot be successful if effective and efficient communication strategy is not implemented. The basic requirements that are required from communication links with respect to communication aims can be defined by using the principles and rules of quality management. By respecting these requirements, it is possible to provide an appropriate mix of communication tools in the strategic planning of communication events. Selecting and setting effective communication tools can be made by methods of multi-criteria evaluation of alternatives. For this objective it is possible to use the AHP method, which takes into account the specifics of the decision-making process in the conditions communication management development projects. Better communication of quality management in projects aimed at regional development can be obtained by applying these methods. The aim of the paper is the proposal of one possible solution methodologies optimal choice of communication tools in the context of strategic communication planning regional development projects.